Integration of generic indicators for quality management in hospital information systems - Rath, Sabine; Heuer, Carsten; Alle, Werner; Bach, Alfons; Bischoff, B.; Bonsanto, Matteo Mario; Borneff-Lipp, M.; Brüssau, Jürgen; Haux, Reinhold; Kunze, Stefan; Linderkamp, Otwin; Middeke, Martin (International journal of medical informatics, 1999)
Hospital information systems may contribute in different ways to quality management activities such as monitoring of quality indicators. Most existing quality management activities in hospitals are adjusted to a special medical field or particular disease. These activities often run simultaneously with other procedures and the documentation of patient care. To determine an interdisciplinary integrated quality management procedure, a pilot study was carried out at the Neurosurgery Department and Neonatology Division of the Medical Center of the University of Heidelberg. Predefined generic indicators that may be integrated in an existing information system and used in hospital routine were the basis of this project. The aim of the study was to support the quality management with periodic reports of these indicators. The pilot study showed that there were barriers along the path to an integrated generic quality management. To meet the requirements of routine monitoring, using predefined generic indicators of hospital care, much integration effort, directed at organizational aspects of information processing and information systems architecture, is still needed.